Effects of disturbances by forest elephants on diversity of trees and insects in tropical rainforests on Mount Cameroon - Maicher, Vincent; Delabye, Sylvain; Murkwe, Mercy; Doležal, Jiří; Altman, Jan; Kobe, Ishmeal N; Desmist, Julie; Fokam, Eric B; Pyrcz, Tomasz; Tropek, Robert (Scientific reports, 2020)
Natural disturbances are essential for tropical forests biodiversity. In the Afrotropics, megaherbivores have played a key role before their recent decline. Contrastingly to savanna elephants, forest elephants' impact on ecosystems remains poorly studied. Few decades ago, forests on Mount Cameroon were divided by lava flows, not being crossed by a local population of forest elephants until now. We assessed communities of trees, butterflies and two guilds of moths in the disturbed and undisturbed forests split by the longest lava flow. We surveyed 32 plots, recording 2025 trees of 97 species, and 7853 insects of 437 species. The disturbed forests differed in reduced tree density, height, and high canopy cover, and in increased DBH. Forest elephants' selective browsing and foraging also decreased tree species richness and altered their composition. The elephant disturbance increased butterfly species richness and had various effects on species richness and composition of the insect groups. These changes were likely caused by disturbance-driven alterations of habitats and species composition of trees. Moreover, the abandonment of forests by elephants led to local declines of range-restricted butterflies. The recent declines of forest elephants across the Afrotropics probably caused similar changes in forest biodiversity and should be reflected by conservation actions.
Keywords: Insecta; stromy; sloni; Elephants; Tropical Climate; Animals; Cameroon; tropické klima; Trees; hmyz; Rainforest; biodiverzita; zachování přírodních zdrojů; Biodiversity; zvířata; Conservation of Natural Resources; deštný prales; Kamerun